A novel OCT servoing control method for endomicroscopy surface scanning. (May 2023) - Xu, Xingfeng; Tang, Rongnian; Zuo, Siyang
Highlights: Position-based OCT servoing control guides the surface scanning and maintains constant contact in real time. The control scheme reduces the influence of probe motion and the pCLE images are clear withot shadow. A new method to detect the position of the tissue surface by OCT, accurately measures the distance between probe and tissue. Abstract: Probe-based confocal laser endomicroscopy (pCLE) enables cell-level visualization for in-vivo tissue of the organ surface in real time. However, an image sequence is needed to generate a large-scale mosaic because the field of view (FOV) of pCLE is restricted. Image mosaicking solves the small FOV issue but only for high-quality pCLE images. The key to acquiring high-quality images is maintaining a constant contact distance even if the surface of the tissue is significantly rough. In this work, optical coherence tomography (OCT) is used to perform surface scanning by maintaining constant contact between the probe tip and the tissue. We proposed a distance detection method to find the position of the tissue surface in OCT images and used a position-based OCT servoing control scheme to guide the surface scanning. Experimental results show that the proposed control scheme with OCT guidance can obtain a large and clear circular mosaic (the diameter is 1 mm). The distance between the probe tip and the tissue is stabilized at the imaging position with distance variance less than 40 μm. The area of mosaics for a spiral trajectory with the proposed control scheme is 8.61 mm 2 . The proposed control scheme has a high potential to collect a clear pCLE image sequence by maintaining a constant distance between the probe tip and the tissue.